Foreign Shareholdings Impact on Credit Risks of Acquired Local Bank in Indonesia - Aswin Rivai, Rina Indiastuti, Adhy Firdaus (International Journal of Advanced Science and Technology, 2020)
The research investigate the impact of foreign shareholding originated from developed anddeveloping countries on the credit risks of acquired local banks in Indonesia during 2007-2017 byincluding Corporate Governance as a moderating variable. This research used data of 29commercial banks acquired by foreign shareholders. A panel regression model with generalized leastsquare is applied to examine the effects of percentages of foreign shareholdings on credit risks of theacquired local banks. This research concludes that foreign shareholdings decrease credit risks ofacquired local banks only if the foreign shareholders is majority shareholders and originated fromdeveloped countries. The minority shareholders from developing countries increase credit risks.Furthermore, increase in the size of the board of directors has no impacts on credit risks. Finally, thepresence of foreign director originated from more developed countries strengthening the effect ofpercentage of foreign shareholdings on decreasing the credit risks of the acquired local banks.Overall, the originality of this research is the findings that both the percentages of foreignshareholdings and its country of origin are two combined factors that cannot be separated in affectingcredit risks of its acquired local bank and the fact of significant positive moderating effect of foreigndirector originated from developed countries. As policy consideration, monetary authority need toperform strict due diligence on prospective foreign shareholders specifically originated fromdeveloping countries, to encourage investing by shareholders from more developed countries andadvise banks to maintain the existence of foreign director.